REVITALISASI LAYANAN BIMBINGAN DAN KONSELING DI PESANTREN - Ach. Firman Ilahi; Moh. Hafid (Konseling At-Tawazun : Jurnal Kajian Bimbingan dan Konseling Islam, 2024)
Islamic boarding schools as traditional Islamic educational institutions have an important role in shaping the character of students. However, so far attention to the development of psy chological aspects and mental well-being of students is still less than optimal, even though this is very important to support the students’ learning process. Therefore, to face the com plex challenges of a rapidly developing era, it is necessary to revitalize guidance and counse ling services. The aim of this research is to describe the revitalization of guidance and coun seling services in Islamic boarding schools. This research uses the library research method. This research produces an elaboration on the vital and integral role of counseling guidance services in Islamic boarding schools. That counseling guidance services must be a consulta tion service for students, as a reactive measure for violations committed by students, and co unseling guidance services as an evaluative action to measure the level of success of the ser vices provided. This has implications for the psychological, emotional, spiritual, intellectual and social aspects of the lives of students in Islamic boarding schools.